ANALISIS IMPLEMENTASI NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR CONSUMER GOODS - Ni Luh Tiya Arini; Ni Nyoman Ayu Suryandari; A.A. Putu Gde Bagus Arie Susandya (Journal of Applied Management and Accounting Science, 2019)
Company value is the company's performance which is reflected by the price of shares formed by the demand and supply of capital markets that reflect the public's assessment of the company's performance. Increasing company value is a long-term goal that the company should have achieved that will be reflected in the stock market price. This study aims to determine the effect of corporate social responsibility, intellectual capital, dividend policy and the ratio of solvency to firm value. The sample in this study were 18 consumer goods sector companies listed on the Indonesia Stock Exchange for the 2016-2018 period. Determination of the sample using purposive sampling technique. The analytical tool used is multiple linear regression analysis. The results showed that the variable corporate social responsibility did not affect the value of the company, intellectual capital variables, dividend policy and solvency ratios had a positive effect on firm value.